3D Periodic Ion Transport Channel to Suppress Top Deposition toward Stable Lithium Metal Anode. Issue 8 (3rd April 2020) - Pan, Linhai; Wang, Jian; Luo, Zhifu; Zhao, Zehua; Li, Yanyan; Egun, Ishioma; He, Haiyong
Abstract: 3D structures have been widely used to suppress dendritic growth for stabilizing lithium metal anode. Unfortunately, it is hard to avoid lithium metal depositing on top of the framework, causing framework to lose its function. Here, we constructed a 3D periodic TiO2 framework (3D‐TiO2 ) on copper foil using polystyrene beads as template. The poor conductivity of TiO2 makes metallic lithium to nucleate on copper surface under framework. Combining with 3D periodic channels for fast ion transport, lithium metal gradually filled the whole space of framework. No lithium metal appeared on surface of 3D‐TiO2 electrode before filling up inner space. Meanwhile, large space provided by interconnected framework can ensure high loading of lithium, thereby suppressing the volume fluctuation during cycling. Additionally, batteries assembled by 3D‐TiO2 electrode exhibited excellent rate capability, owning to the fast ion transport supplied by 3D periodic structure. We believe that the combination of high capacity and frequency response in lithium metal anode could meet the challenge of the currently available devices. Abstract : Stop the dendrites : In this study, 3D periodic TiO2 framework (3D‐TiO2 ) on copper foil was fabricated using polystyrene beads as template. The conductivity difference makes it possible for lithium to realize the selective deposition from bottom to top. Meanwhile, the large space provided by interconnected framework can ensure high loading of lithium, thereby suppressing volume fluctuation. Additionally, the 3D periodic structure can promote ions transport, resulting in excellent rate capability.